2012
DOI: 10.1590/s0004-27302012000700004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma homocysteine level according to the C677T and A1298C polymorphism of the enzyme MTHRF in type 2 diabetic adults

Abstract: Objective: To determine plasma homocysteine levels during fasting and after methionine overload, and to correlate homocysteinemia according to methylenetetrahydrofolate reductase (MTHFR) polymorphism in type 2 diabetic adults. Subjects and methods: The study included 50 type 2 diabetic adults (DM group) and 52 healthy subjects (Control group). Anthropometric data, and information on food intake, serum levels of vitamin B 12 , folic acid and plasma homocysteine were obtained. The identification of C677T and A12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…To our knowledge, this is the first meta-analysis of prevalence of HHcy in China, and the results showed that the overall estimate of HHcy prevalence was 27.5%. The pooled prevalence is similar to that reported in Brazil [ 24 ] and Lebanon [ 25 ], but higher than that reported in Switzerland [ 26 ], Costa Rica [ 27 ], and Korea [ 28 ], and lower than that reported in Iran [ 29 ], Algeria [ 30 ], and coastal West Africa [ 11 ]. The different prevalence rates reported in various countries could be due to different population inclusion criteria, genetic backgrounds, as well as differences in HHcy risk factor profiles (such as nutrition status, environment exposures, and lifestyles) in the population of each country.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this is the first meta-analysis of prevalence of HHcy in China, and the results showed that the overall estimate of HHcy prevalence was 27.5%. The pooled prevalence is similar to that reported in Brazil [ 24 ] and Lebanon [ 25 ], but higher than that reported in Switzerland [ 26 ], Costa Rica [ 27 ], and Korea [ 28 ], and lower than that reported in Iran [ 29 ], Algeria [ 30 ], and coastal West Africa [ 11 ]. The different prevalence rates reported in various countries could be due to different population inclusion criteria, genetic backgrounds, as well as differences in HHcy risk factor profiles (such as nutrition status, environment exposures, and lifestyles) in the population of each country.…”
Section: Discussionsupporting
confidence: 83%
“…Although studies have claimed that the prevalence of HHcy is higher in northern areas, the results from our study showed an even higher rate than previously reported. In addition, the prevalence was higher than those of many other places in the world, such as Brazil [22], Lebanon [23], Korea [24] and West Africa [25]. One of the major possible reasons for the high prevalence of HHcy might be the different dietary habits in rural Northeast China.…”
Section: Discussionmentioning
confidence: 94%
“…One study of a cohort of Brazilian subjects did not find any association between the I/D polymorphism of the ACE gene and patients with T2DM and metabolic syndrome according to the criteria of the World Health Organization (27), and there are no studies reporting the risk of individuals with this polymorphism developing diabetes. Although there is a Brazilian study that correlates homocysteine levels in patients with and without T2DM to the polymorphism of the MTHFR gene (28), there are no studies showing any association of this gene with the risk of developing diabetes in the same population.…”
Section: Discussionmentioning
confidence: 99%